A mechanically resilient soft hydrogel improves drug delivery for treating post-traumatic osteoarthritis in physically active joints - Nitin Joshi; Jing Yan; Mickael Dang; Kai Slaughter; Yufeng Wang; Dana Wu; Trevor Ung; Nutan Bhingaradiya; Virja Pandya; Mu Xian Chen; Shahdeep Kaur; Sachin Bhagchandani; et al. (Proceedings of the National Academy of Sciences, 2025)
Intra-articular delivery of disease-modifying osteoarthritis drugs (DMOADs) is likely to be most effective in the early stages of post-traumatic osteoarthritis (PTOA), when symptoms are minimal, and patients remain physically active. To ensure effective therapy, DMOAD delivery systems therefore must withstand repeated mechanical loading without altering the kinetics of drug release. While soft materials are typically preferred for DMOAD delivery, mechanical loading can compromise their structural integrity and disrupt controlled drug release. In this study, we present a mechanically resilient soft hydrogel that rapidly self-heals under conditions simulating human running while maintaining sustained release of the cathepsin-K inhibitor L-006235, used as a proof-of-concept DMOAD. This hydrogel demonstrated superior performance compared to a previously reported hydrogel designed for intra-articular drug delivery, which, in our study, neither recovered its structure nor maintained drug release under mechanical loading. When injected into mouse knee joints, the hydrogel provided consistent release kinetics of the encapsulated drug in both treadmill-running and nonrunning mice. In a mouse model of severe PTOA exacerbated by treadmill-running, the L-006235 hydrogel significantly reduced cartilage degeneration, whereas the free drug did not. Overall, our data underscore the hydrogel’s potential for treating PTOA in physically active patients.